Is the cellular and molecular machinery docile in the stationary phase of Escherichia coli?. (7th April 2015) - Mehta, Parul; Jovanovic, Goran; Ying, Liming; Buck, Martin
Abstract : The bacterial cell envelope retains a highly dense cytoplasm. The properties of the cytoplasm change with the metabolic state of the cell, the logarithmic phase (log) being highly active and the stationary phase metabolically much slower. Under the differing growth phases, many different types of stress mechanisms are activated in order to maintain cellular integrity. One such response in enterobacteria is the phage shock protein (Psp) response that enables adaptation to the inner membrane (IM) stress. The Psp system consists of a transcriptional activator PspF, negative regulator PspA, signal sensors PspBC, with PspA and PspG acting as effectors. The single molecule imaging of the PspF showed the existence of dynamic communication between the nucleoid-bound states of PspF and membrane via negative regulator PspA and PspBC sensors. The movement of proteins in the cytoplasm of bacterial cells is often by passive diffusion. It is plausible that the dynamics of the biomolecules differs with the state of the cytoplasm depending on the growth phase. Therefore, the Psp response proteins might encounter the densely packed glass-like properties of the cytoplasm in the stationary phase, which can influence their cellular dynamics and function. By comparing the properties of the log and stationary phases, we find that the dynamics of PspF are influenced by the growth phase and may be controlled by the changes in the cytoplasmic fluidity.